Kajian Promosi Kesehatan di Lingkungan Rumah Sakit - Detriana Imeriet Nenobais (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
This study aims to determine health promotion in the hospital environment. The method used is qualitative where the data obtained is analyzed to be described qualitatively. The results obtained that health promotion in the home environment can increase the insight of patients, patient families, and hospital visitors about various diseases and the correct way to prevent them, in addition health promotion in hospitals is an effort by hospitals to improve the ability of patients, families and hospital visitors to be able to play a positive role in efforts to cure and prevent diseases so that they can accelerate the healing and rehabilitation process, improve health, prevent health problems, and develop health efforts through learning according to each socio-culture independently